ANALISIS KANDUNGAN BAKTERI ESCHERIA COLI PADA AIR KOLAM RENANG UMUM DI KOTA MANADO TAHUN 2020 - Diamanis, Celsya Tasya; Maddusa, Sri Seprianto; Joseph, Woodford B. S. (Sam Ratulangi University, 2020)
Tujuan Penelitian: Mengetahui apakah terdapat kandungan bakteri Escherichia coli pada air kolam renang umum di Kota Manado Tahun 2020 dan menentukan apakah memenuhi syarat atau tidak memenuhi syarat. Metode Penelitian: Penelitian ini merupakan jenis penelitian survey deskriptif dengan uji laboratorium. Populasi dalam penelitian ini yaitu kolam renang umum di Kota Manado. Pengambilan sampel dilakukan sore hari setelah kolam renang digunakan oleh pengunjung dengan pengambilan sampel dilakukan pada 3 titik. Hasil Penelitian: Berdasarkan hasil penelitian yang telah dilakukan dari 15 sampel yang dianalisis di Laboratorium BARISTAND Manado dengan metode pengujian Uji MPN (Most Probable Number) menunjukkan hasil 15 sampel air kolam renang jumlah kandungan Escherichia coli yaitu <1 MPN/100ml. Kesimpulan: Kualitas bakteriologis Escherichia coli untuk air kolam renang umum di Kota Manado memenuhi syarat karena tidak terdapat kandungan bakteri Escherichia coli yang menunjukan air kolam renang umum Kota Manado memenuhi syarat yang di tetapkan oleh Permenkes No. 32 Tahun 2017. Kata Kunci : air kolam renang umum, Bakteri Escherichia coli ABSTRACTSwimming pool water quality must be maintained and maintained continuously and regularly so that water can be avoided from microbiological pollution. Based on a research by the Centers for Disease Control (2013), it was found that 161 swimming pools were contaminated with bacteria. Escherichia coli is one of the bacteria as an indicator of the causes of microbiological contamination of swimming pool water quality. The content of Escherichia coli bacteria must comply with regulated requirements so as not to cause health problems. Research purposes find out whether there is a content of Escherichia Coli bacteria in public swimming pool water in Manado City in 2020 and determine whether it meets the requirements or not. Research methods this research is a descriptive survey research type with laboratory tests. The population in this study is a public swimming pool in the city of Manado. Sampling was carried out in the afternoon after the swimming pool was used by visitors with sampling carried out at 3 points. Research result based on the results of research that has been carried out from 15 samples analyzed at the BARISTAND Manado Laboratory with the MPN (Most Probable Number) test method, it shows that the results of 15 swimming pool water samples, the total content of Escherichia coli is <1 MPN / 100ml. Conclusion the bacteriological quality of Escherichia coli for public swimming pool water in Manado City is still safe because there is no Escherichia coli content which shows that Manado City public swimming pool water meets the requirements set by Permenkes No. 32 of 2017. Keywords: Swimming Pool Water Public, Bakteri Escherichia col